Gambaran Tingkat Mindful Self-care pada Mahasiswa Bimbingan dan Konseling Islam (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Mindful self-care is a process that involves awareness and careful assessment of one's internal needs and external demands. The implications of self-care activities that are deliberately carried out specifically can meet needs and demands by providing services for one's well-being. The transition from adolescence to adulthood can be marked by dramatic life changes, such as during college as a student at a university. Students aged 18 and over may face various academic, social, and emotional pressures that can affect their physical and psychological well-being. This research is descriptive quantitative research with a survey type to see an overview of the level of mindful self-care in college students. This research was conducted on 75 Islamic Guidance and Counseling Study Program students at the Da'wah Faculty of UIN Sultan Maulana Hasanuddin Banten. The study results showed that 36% were in the low category, 40% were in the medium category, and 24% were in the high category. Based on this, the average value obtained is 3.76, which indicates that mindful self-care for students of the Guidance and Counseling Study Program, Faculty of Da'wah, Sultan Maulana Hasanuddin Banten State Islamic University, is in the medium category.